1985
DOI: 10.1007/bf00144173
|View full text |Cite
|
Sign up to set email alerts
|

A crop-based rainfall chronology for pre-instrumental record southern California

Abstract: Although measured climatic records begin in California about 1850, agricultural records from the earlier Spanish period can be used to develop information about annual precipitation. This historical material should be used, however, only with a full understanding of the numerous cultural variables that influenced agricultural production. A study by Iynch in 1931, which is widely cited in the literature of Pacific Coast climate reconstruction, contains serious shortcomings because of incorrect assumptions abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 11 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Historical documents yield the highest frequency data out of all the proxy data types. To date, most of the successful historical climatological research has been focused on Europe and southeast Asia, but similar results have been derived for North America (Baron, 1982;Moodie and Catchpole, 1975;Catchpole and Ball, 1981;Rowntree, 1985;Lawson, 1974). Oliver and Kington (1970), Kington (1980), Douglas et al (1978), and Wilson (1985 demonstrated that historical documents can be used for synoptic weather reconstruction for daily and seasonal timescales.…”
Section: Introductionmentioning
confidence: 70%
“…Historical documents yield the highest frequency data out of all the proxy data types. To date, most of the successful historical climatological research has been focused on Europe and southeast Asia, but similar results have been derived for North America (Baron, 1982;Moodie and Catchpole, 1975;Catchpole and Ball, 1981;Rowntree, 1985;Lawson, 1974). Oliver and Kington (1970), Kington (1980), Douglas et al (1978), and Wilson (1985 demonstrated that historical documents can be used for synoptic weather reconstruction for daily and seasonal timescales.…”
Section: Introductionmentioning
confidence: 70%